Bridge publications & website - BRIDGE, Institute of Development Studies (IDS) (Brighton, UK : BRIDGE (Organization))
Virtual bookcase containing all of BRIDGE's publications produced be fore December 2005.
Description based on: Introductory screen
PDF files can be viewed using Adobe Acrobat Reader
Keywords: Women in development; Economic development